Self, peer and teamwork assessment / Rafizan Abdul Razak and Akma Hidayu Dol @ Abdul Wahid - Abdul Razak, Rafizan; Dol @ Abdul Wahid, Akma Hidayu (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Many of the assessments conducted for diploma or degree courses at faculty or university incorporate selfevaluation, teamwork, or group project evaluation. These methods of assessments allow students to be more effective, responsive, and responsible in terms of their contribution, roles, and performance in any task or project given by their lecturer or supervisor. According to Capan Melser et al., (2020), in peer assessment, students are directly engaged in training self-monitoring, self-evaluation, and task selection skills, in all of which the students have much control over the learning tasks they are engaged in.